2021
DOI: 10.1142/s1793524521500881
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis and optimal control for Chikungunya virus with two routes of infection with nonlinear incidence rate

Abstract: Chikungunya fever, caused by Chikungunya virus (CHIKV) and transmitted to humans by infected Aedes mosquitoes, has posed a global threat in several countries. In this paper, we investigated a modified within-host Chikungunya virus (CHIKV) infection model with antibodies where two routes of infection are considered. In a first step, the basic reproduction number [Formula: see text] was calculated and the local and global stability analysis of the steady states is carried out using the local linearization and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It can be easily shown that W 0 = {E 0 }. Using LaSalle's invariance principle [26] (see [8,11,12,27] for some examples), one deduces that E 0 is globally asymptotically stable once R 0 ≤ 1.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be easily shown that W 0 = {E 0 }. Using LaSalle's invariance principle [26] (see [8,11,12,27] for some examples), one deduces that E 0 is globally asymptotically stable once R 0 ≤ 1.…”
Section: 4mentioning
confidence: 99%
“…Several works qualitatively proposed and studied some mathematical models describing the dynamical behaviour of infectious disease transmission (see, for example, [3][4][5][6][7][8][9]). In particular, the HIV epidemic models with constant coefficients have been analysed in several works (see, for example, [10][11][12][13]). However, seasonality is very repetitive in each of the ecological, biological, and human systems [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several mathematical models have been presented in the CHIKV infection literature to describe the evolution of disease transmission in a population over time or to describe the population growth of chikungunya virus within-host at each stage, see for example [1,3,18]. Modelling, mathematical analysis and optimal control for this virus have been studied by El Hajji et al in [19,20].…”
Section: Chikv Model With Latencymentioning
confidence: 99%
“…It can be easily shown that W1 = { Ē} . Using LaSalle's invariance principle [14] (see [15,16,17,9,10,11,18,19] for more applications), one can easily deduce that Ē is GAS when R ≤ 1. Then the solution of system (2.1) converges to Ē since t → +∞.…”
Section: Global Stability Analysismentioning
confidence: 99%
“…The main indicator in the spread of an epidemic is the force of infection or the rate at which a susceptible person becomes infected. The prediction models are mainly based on deterministic principles such as SIR or SEIR [6,7,8,9,10,11]. Recent SARS-CoV-2 models are often derived from the SIR model by adding a population of infected non-infectious E (or exposed) individuals who are therefore not contagious.…”
Section: Introductionmentioning
confidence: 99%